NMR structure of the histidine kinase domain of the E. coli osmosensor EnvZ - Tanaka, Toshiyuki; Saha, Soumitra K.; Tomomori, Chieri; Ishima, Rieko; Liu, Dingjiang; Tong, Kit I.; Park, Heiyoung; Dutta, Rinku; Qin, Ling; Swindells, Mark B.; Yamazaki, Toshimasa; Ono, Akira M.; et al. (Nature (London), 1998)
Bacteria live in capricious environments, in which they must continuously sense external conditions in order to adjust their shape, motility and physiology 1 . The histidine–aspartate phosphorelay signal-transduction system (also known as the two-component system) is important in cellular adaptation to environmental changes in both prokaryotes and lower eukaryotes 2 , 3 . In this system, protein histidine kinases function as sensors and signal transducers. The Escherichia coli osmosensor, EnvZ, is a transmembrane protein with histidine kinase activity in its cytoplasmic region 2 . The cytoplasmic region contains two functional domains 4 : domain A (residues 223–289) contains the conserved histidine residue (H243), a site of autophosphorylation as well as transphosphorylation to the conserved D55 residue of response regulator OmpR, whereas domain B (residues 290–450) encloses several highly conserved regions (G1, G2, F and N boxes) and is able to phosphorylate H243. Here we present the solution structure of domain B, the catalytic core of EnvZ. This core has a novel protein kinase structure, distinct from the serine/threonine/tyrosine kinase fold, with unanticipated similarities to both heat-shock protein 90 and DNA gyrase B.